# What is 4x plus 12y equal 48

QUESTION POSTED AT 06/12/2019 - 03:40 PM

QUESTION POSTED AT 06/12/2019 - 03:40 PM

4x+12y=48
12y=48-4x
Y=4-3x
Steps
1.subtract 4x to the other side
2.divide 12 to all numbers
Answer is : y=4-3x

180 degrees I mean I do not know how to really explain it its based on the amount of sides a shape has and the sum of all 3 interior angles is 180

ANSWERED AT 28/01/2020 - 01:06 AM

QUESTION POSTED AT 28/01/2020 - 01:06 AM

**Answer:**

The graph of the circle and function g(x) intersects at the positive and negative x-coordinates as well as at the origin.

**Step-by-step explanation:**

The equation of circle is given as:

also the graph of the function g(x) is given by:

We are given a set of values in a table as:

x g(x)

−4 −4

−2 −2

2 2

Hence, the function g(x) could be computed with the help of slope intercept form of a equation as:

y=mx+c; where m denotes the slope of the line and c denotes the y intercept.

when x=-4 g(x)=y=-4

-4=-4m+c

also when x=-2 then y=g(x)=-2

-2=-2m+c

on solving the above two equations using elimination method we get,

m=1 and c=0

hence, y=g(x)=x

Now we are asked tgo find whether the graph of the circle and g(x) intersect each other or not.

**Clearly from the graph we could see that the graph of the circle and function g(x) intersects at the positive and negative x-coordinates as well as at the origin.**

ANSWERED AT 28/01/2020 - 12:50 AM

QUESTION POSTED AT 28/01/2020 - 12:50 AM

No.

x^3 * x^3 * x^3 > x^3*3*3

x^3 * x^3 * x^3 = 19683

whereas x^3*3*3 = 7.626 (rounded to 3 decimal places)

x^3 * x^3 * x^3 > x^3*3*3

x^3 * x^3 * x^3 = 19683

whereas x^3*3*3 = 7.626 (rounded to 3 decimal places)

ANSWERED AT 28/01/2020 - 12:49 AM

QUESTION POSTED AT 28/01/2020 - 12:49 AM

7/20 is equal to 0.35 or can also be equal to 35% of the whole.

ANSWERED AT 28/01/2020 - 12:49 AM

QUESTION POSTED AT 28/01/2020 - 12:49 AM

4/6 , 6/9 would be 2 examples

ANSWERED AT 28/01/2020 - 12:44 AM

QUESTION POSTED AT 28/01/2020 - 12:44 AM

The correct answer is 2.

4x^2=8x

4x^2-8x=8x-8x

4x^2-8x=0

4x(x-2)=0

x=0 or x=2

Therefore x=2

4x^2=8x

4x^2-8x=8x-8x

4x^2-8x=0

4x(x-2)=0

x=0 or x=2

Therefore x=2

ANSWERED AT 28/01/2020 - 12:36 AM

QUESTION POSTED AT 28/01/2020 - 12:36 AM

Set the denominator equal to 0 and solve for x to find the restricted value

4x + 5 = 0

x = -5/4

domain: x ≠ -5/4

or in interval notation: (-∞, -5/4) U (-5/4, ∞)

4x + 5 = 0

x = -5/4

domain: x ≠ -5/4

or in interval notation: (-∞, -5/4) U (-5/4, ∞)

ANSWERED AT 28/01/2020 - 12:32 AM

QUESTION POSTED AT 28/01/2020 - 12:32 AM

That would be C.

20x + 5y = 50

5y = - 20x + 50

y = -20/5x + 50/5

y = - 4x + 10

now in y = mx + b form. the m represents ur slope and the b represents ur y intercept. So here, u have a slope of -4 and a y intercept of 10.

20x + 5y = 50

5y = - 20x + 50

y = -20/5x + 50/5

y = - 4x + 10

now in y = mx + b form. the m represents ur slope and the b represents ur y intercept. So here, u have a slope of -4 and a y intercept of 10.

ANSWERED AT 28/01/2020 - 12:31 AM

QUESTION POSTED AT 28/01/2020 - 12:31 AM

The answer is -3 because if you plug in the values for the letters you would get -24/2(4)

Once you simplify the expression, you will get -24/8

24/8 is 3 and you take the sign of the larger number which is negative

so your answer is (-3)

Hope i helped

Once you simplify the expression, you will get -24/8

24/8 is 3 and you take the sign of the larger number which is negative

so your answer is (-3)

Hope i helped

ANSWERED AT 28/01/2020 - 12:05 AM

QUESTION POSTED AT 28/01/2020 - 12:05 AM

1.

B becacause is the only with logic

2.

A because it is imposible to r = s

B becacause is the only with logic

2.

A because it is imposible to r = s

ANSWERED AT 27/01/2020 - 11:59 PM

QUESTION POSTED AT 27/01/2020 - 11:59 PM

Y = -1.3x + 9

y = –4x + 10

_______________

0=2.7x-1

2.7x=1

x=0.37

y = –4x + 10

_______________

0=2.7x-1

2.7x=1

x=0.37

ANSWERED AT 27/01/2020 - 11:58 PM

QUESTION POSTED AT 27/01/2020 - 11:58 PM

3(8-4x) < 6(x-5)

24 -12x < 6x -30

24 +30 < 6x +12x

54 < 18x

54/18 < x

3 < x

so the number line which represents the solution set for given inequality started with 3 but is greater than 3 and go away till plus infinity

hope this will help you

24 -12x < 6x -30

24 +30 < 6x +12x

54 < 18x

54/18 < x

3 < x

so the number line which represents the solution set for given inequality started with 3 but is greater than 3 and go away till plus infinity

hope this will help you

ANSWERED AT 27/01/2020 - 11:57 PM

QUESTION POSTED AT 27/01/2020 - 11:57 PM

Because even though 'a' and 'b' are rational, and their squares are

also rational, that doesn't guarantee that the**sum** of their squares

has a rational square root.

Examples:

1 and 2

Sum of squares = 5

√5 is irrational

2 and 3

Sum of squares = 13

√13 is irrational

4 and 5

Sum of squares is 41

√41 is irrational

'c' is rational only when 'a', 'b', and 'c' form a . . . . . wait for it . . . . .

a 'Pythagorean triple'.

Examples:

3 and 4

Sum of squares is 25

√25 = 5 is rational yay

5 and 12

Sum of squares is 169

√169 = 13 is rational yay

also rational, that doesn't guarantee that the

has a rational square root.

Examples:

1 and 2

Sum of squares = 5

√5 is irrational

2 and 3

Sum of squares = 13

√13 is irrational

4 and 5

Sum of squares is 41

√41 is irrational

'c' is rational only when 'a', 'b', and 'c' form a . . . . . wait for it . . . . .

a 'Pythagorean triple'.

Examples:

3 and 4

Sum of squares is 25

√25 = 5 is rational yay

5 and 12

Sum of squares is 169

√169 = 13 is rational yay

ANSWERED AT 27/01/2020 - 11:50 PM

QUESTION POSTED AT 27/01/2020 - 11:50 PM

**Answer:**

**There are infinite number of solution**

**Step-by-step explanation:**

We have to tell the number of solution of given equation

12x+1=3(4x+1)-2

We solve the expression on the right hand side

i.e. 3(4x+1)-2

= 12x+3-2

= 12x+1

Which is equal to the expression on the left hand side.

Hence, for any value of x right hand side equals left hand side

** Hence, there are infinite number of solution**

ANSWERED AT 27/01/2020 - 11:49 PM

QUESTION POSTED AT 27/01/2020 - 11:49 PM

5 and 7..........................

ANSWERED AT 27/01/2020 - 11:48 PM

QUESTION POSTED AT 27/01/2020 - 11:48 PM

-2x² ( 4x-3)

To simplify more easily just use the distributive property

(-2x²)(4x) + (-2x²)(-3)

Now you can multiply and save the sign

**-8x³ + 6x²**

**Have a great week :)**

ANSWERED AT 27/01/2020 - 01:41 AM

QUESTION POSTED AT 27/01/2020 - 01:41 AM

Are there any options? like is it multiple choice or not?

ANSWERED AT 27/01/2020 - 01:39 AM

QUESTION POSTED AT 27/01/2020 - 01:39 AM

Answer:

Positive

Step-by-step explanation:

ANSWERED AT 27/01/2020 - 01:32 AM

QUESTION POSTED AT 27/01/2020 - 01:32 AM

**Answer:**

**Range** defined as the complete set of possible values of the dependent variable,

or

**The range is defined as the resulting y-values we get after substituting all the possible values of x from domain.**

Given the function:

Also, x ∈Domain = {-1, 0, 1, 2, 3}

**For x = -1;**

y = 4(-1)-1 = -4 -1 = **-5**

**For x = 0;**

y = 4(0)-1 = 0 -1 = **-1**

**For x = 1;**

y = 4(1)-1 = 4-1 =**3**

**For x = 2;**

y = 4(2)-1 = 8-1 =**7**

**For x = 3;**

y = 4(3)-1 = 12-1 =**11**

**Therefore, the range of the function are the set of all values of y i,e **

**Range = {-5, -1, 3, 7 , 11}**

ANSWERED AT 27/01/2020 - 12:42 AM

QUESTION POSTED AT 27/01/2020 - 12:42 AM

You skiped one operator.

I assume that the function is f(n+1) = f(n) - 2.

f(1) = 10

f(2) = f(1) - 2 = 10 - 2 = 8

f(3) = f(2) - 2 = 8 - 2 = 6

f(4) = f(3) - 2 = 6 - 2 = 4

f(5) = f(4) - 2 = 4 -2 = 2

So the sequence, is 10, 8, 6, 4, 2, ... [option d]

I assume that the function is f(n+1) = f(n) - 2.

f(1) = 10

f(2) = f(1) - 2 = 10 - 2 = 8

f(3) = f(2) - 2 = 8 - 2 = 6

f(4) = f(3) - 2 = 6 - 2 = 4

f(5) = f(4) - 2 = 4 -2 = 2

So the sequence, is 10, 8, 6, 4, 2, ... [option d]

ANSWERED AT 27/01/2020 - 12:40 AM

QUESTION POSTED AT 27/01/2020 - 12:40 AM

We have two unknowns from the equation therefore, two equations are needed. These equations are:

3x + y = 9

y = –4x +10

To solve for y, we first substitute the second equation to the first one.

3x + –4x +10= 9

x = 1

We substitute the value of x to either of the equations and solve for y.

y = –4(1) +10

**y = 6**

3x + y = 9

y = –4x +10

To solve for y, we first substitute the second equation to the first one.

3x + –4x +10= 9

x = 1

We substitute the value of x to either of the equations and solve for y.

y = –4(1) +10

ANSWERED AT 27/01/2020 - 12:40 AM

QUESTION POSTED AT 27/01/2020 - 12:40 AM

we have that

using a graph tool

see the attached figure

**statements**

**case a)** The domain is {x|x ≤ –2}-------> Is False

the domain is all real numbers---------> the interval (-∞,∞)

**case b)** The range is {y|y ≤ 6}.------> Is True

The range is the interval (-∞,6]

**case c)** The function is increasing over the interval (–∞ , –2).-----> Is True

See the attached figure

**case d)**The function is decreasing over the interval (−4, ∞).-----> Is False

In the interval (-4,-2) the function is increasing and in the interval (-2,∞) the function is decreasing (See the attached figure)

**case e)**The function has a positive y-intercept.------> Is True

The value of y-intercept is

ANSWERED AT 27/01/2020 - 12:32 AM

QUESTION POSTED AT 27/01/2020 - 12:32 AM

**Answer: The answer is (b). **

**Step-by-step explanation: **Let us consider a circle with centre "O" and radius OA=OB=r units. We know that the circumference of a circle is so the circumference of Circle 'C' is given by

Also, let us central angles of equal size of 'n°', the the number of sectors formed is given by

Now, the formula for arc length of a sector is given by

∴

Thus, **(b) is the correct option.**

ANSWERED AT 27/01/2020 - 12:31 AM

QUESTION POSTED AT 27/01/2020 - 12:31 AM

**Answer:**

and

**Step-by-step explanation:**

Let

x-------> the first odd number

x+2----> the second consecutive odd number

we know that

----> linear equation that represent the situation

solve for x

Multiply by both sides

Find the second consecutive odd number

ANSWERED AT 27/01/2020 - 12:25 AM

QUESTION POSTED AT 27/01/2020 - 12:25 AM

From the data, you have to share 5 pieces among 3 people.

so each person will get 5/3

5/3 = 1.7

so each person will get 5/3

5/3 = 1.7

ANSWERED AT 26/01/2020 - 11:53 PM

QUESTION POSTED AT 26/01/2020 - 11:53 PM

ANSWERED AT 26/01/2020 - 11:46 PM

QUESTION POSTED AT 26/01/2020 - 11:46 PM

A+b+c=69

a=b+8

b=a-8

c=a/5

a is 11 (3+8= 11 which is a)

b is 3 (11-8=3 which is b)

c is 55. (11 x 5=55 which is c)

a=b+8

b=a-8

c=a/5

a is 11 (3+8= 11 which is a)

b is 3 (11-8=3 which is b)

c is 55. (11 x 5=55 which is c)

ANSWERED AT 26/01/2020 - 11:44 PM

QUESTION POSTED AT 26/01/2020 - 11:44 PM

The answer is 2.

p=3

3^2+5(4 x 3)= 2

p=3

3^2+5(4 x 3)= 2

ANSWERED AT 26/01/2020 - 11:32 PM

QUESTION POSTED AT 26/01/2020 - 11:32 PM

2 a + b = 15.7

Since the sides are equal length, the equation is:

**2 · 6.3 + b = 15.7**

We can solve it:

12.6 + b = 15.7

b = 15.7 - 12.6

**b = 3.1 cm**

Since the sides are equal length, the equation is:

We can solve it:

12.6 + b = 15.7

b = 15.7 - 12.6

ANSWERED AT 26/01/2020 - 11:29 PM

QUESTION POSTED AT 26/01/2020 - 11:29 PM

If we use the last equation:

2 x = 18

x = 18 : 2

**x = 9**

Then we will put it in another equation:

x - 2 y = 3

9 - 2 y = 3

- 2 y = 3 - 9

- 2 y = -6

y = -9 : ( -3 )

**y = 3**.

The solution is :**D ) ( 9, 3 )**

2 x = 18

x = 18 : 2

Then we will put it in another equation:

x - 2 y = 3

9 - 2 y = 3

- 2 y = 3 - 9

- 2 y = -6

y = -9 : ( -3 )

The solution is :

ANSWERED AT 26/01/2020 - 11:21 PM

QUESTION POSTED AT 26/01/2020 - 11:21 PM